Penerapan Art Therapy untuk Menurunkan Depresi pada Lansia di Panti Werdha X - Ayu Eka Permatasari; Samsunuwiyati Marat; Meiske Y. Suparman (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2017)
Aging process on elderly can be challenging. Elderly who lives with their family can enjoy happiness and independent live. But, it is different with elderly who lives in a nursing home. Elderly who live in a nursing home often feel lonely, lack of activity, and experience stress to depression. They tend to show symptoms of depression which are sense of helplessness, avoidance of social interaction, experience physical complaints such as headaches, back pain, digestive disorders, and indisgestion. This research is aimed to know whether the application of art therapy can reduce depression on the elderly who lives in a nursing homes. Art therapy intervention with with drawing and coloring methods were chosen because it can be applied to individual of all ages. This intervention is aimed to express feelings, changing negative thoughts, and to be able to more recognize them selves. Participants of this research were 3 elderly who live in nursing homes. The intervention was conducted for 12 sessions. The results were being measured by comparing the pretest-posttest score of Geriatric Depression Scale (GDS). After the intervention was conducted, all participants showed reducing score of depression on GDS on posttest score. During the intervention, all participant also showed process of increasing expressions on their artwork. The results also indicated changes of their behaviors such as increasing social interaction.Keywords: Art therapy, Elderly, Depression, Gerontology, Nursing homes.